A posição sadomasoquista da mulher : suas interfaces entre o amor e o ódio no vínculo materno : uma leitura psicanalítica - Prestes, Vivian Rafaella (2015)
This study investigates the sadomasochist psychodynamic of the women from their emotional relationships. The central question guiding this work is what keeps them in such a relationship or what is the unconscious satisfaction which ensures adherence to such symptoms. We aimed also is to separate the idea of the sadomasochism with cruelty related to sexual practices, point of view as well exploited by some literature books, such as the work Fifty Shades of Grey written by E. L. James. For both, we have two true and distinct stories which come of sadomasochistic positions in its various configurations and arrangements. The reports have been analyzed in the light of Freud's theory; therefore, we consider the manifest content, as well as the latent content. The methodology used is the search with the psychoanalytic method, which is based on the concepts of unconscious, free association, and floating attention. Here is the origin of the term sadism and masochism, from literature and Freud's contribution to understanding this phenomenon. We emphasize the importance of ambivalent feelings that the child directs the mother, as well as her experience pre-oedipal with the maternal figure, experiences that contribute as a nodal point of this weft.